2003
DOI: 10.1046/j.1432-1033.2003.03673.x
|View full text |Cite
|
Sign up to set email alerts
|

Exo‐mode of action of cellobiohydrolase Cel48C from Paenibacillus sp. BP‐23

Abstract: Sequence analysis of a Paenibacillus sp. BP-23 recombinant clone coding for a previously described endoglucanase revealed the presence of an additional truncated ORF with homology to family 48 glycosyl hydrolases. The corresponding 3509-bp DNA fragment was isolated after gene walking and cloned in Escherichia coli Xl1-Blue for expression and purification. The encoded enzyme, a cellulase of 1091 amino acids with a deduced molecular mass of 118 kDa and a pI of 4.85, displayed a multidomain organization bearing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 38 publications
2
24
0
Order By: Relevance
“…Similarities between Myxobacter sp. AL-1 and different members of the Bacilli (in particular Bacillus licheniformis), in terms of unique structural similarities in family 48 glycosyl hydrolases (25) but also in terms of sequence similarities of other types of cellulases (22), have been reported previously.…”
Section: Discussionsupporting
confidence: 53%
“…Similarities between Myxobacter sp. AL-1 and different members of the Bacilli (in particular Bacillus licheniformis), in terms of unique structural similarities in family 48 glycosyl hydrolases (25) but also in terms of sequence similarities of other types of cellulases (22), have been reported previously.…”
Section: Discussionsupporting
confidence: 53%
“…The introduction of CBM3a into either Cel48F or Cel9G improved their activity on Avicel at the apparent expense of their activity on more tractable substrates, such as PAS-cellulose. Indeed, GH48 and GH9-CBM3c en- zymes appended with an efficient CBM3 (generally CBM3b) have been discovered in various bacteria (4,15,28,31). Acetivibrio cellulolyticus was also found to produce an enzymecontaining scaffolding protein that exhibits one GH9 module (not associated with a CBM3c), one CBM3b, and seven cohesin modules (8).…”
Section: Discussionmentioning
confidence: 99%
“…Exo-type cellulases (cellobiohydrolases) are divided into two groups: enzymes that recognize the reducing end (mainly belonging to families GH7 and GH48), and enzymes that recognize the nonreducing end (mainly belonging to GH6 and GH48) (34)(35)(36)(37). It has been reported that organisms that harbor both types of exo-type cellulases along with an endo-type enzyme, such as Thermomonospora fusca and Trichoderma reesei (34), display relatively high efficiency in cellulose degradation.…”
Section: Tc-chid(⌬s) or Tc-chid(⌬bd)mentioning
confidence: 99%